The Walpurgis Night): A New Variation on the Theme of the Holocaust. Several Suggestions as for the Future Reception of the Film - Skibska, Anna Maria (Poznańskie Studia Slawistyczne, 2017)
In the essay, I make an attempt to present several ways, in which the Western canon of literature, music, and cinema has influenced Noc Walpurgi. With regard to this, Marcin Bortkiewicz’s film turns out to be a work made of many citations, in Walter Benjamin’s terms, drawn extensively on Goethe’s Faust, Mann’s The Magic Mountain, Bulgakov’s The Master and Margarita, Wagner’s Ride of the Valkyries, and Puccini’s Turandot, and the film noir poetics elaborated in the 40s and 50s of the twentieth century. Based on Magdalena Gauer’s monodrama Diva, Noc Walpurgi illuminates in the highly expressionist manner an alienated, cynical, and despotic psyche of Nora Sadler, a great opera singer, who is tormented by the Holocaust past.